Pengaruh Kualitas Aplikasi Ruangguru CAMP Terhadap Kepuasan Mahasiswa Study Independent Product Management (Studi Kasus: Efektivitas dan Pengalaman Pengguna) - Laily, Nisfal; Tranggono (Jurnal Serambi Engineering, 2025)
Ruangguru CAMP is a joint programme between Ruangguru and Kampus Merdeka. This programme is in the form of online course learning. The purpose of this study is to determine the extent to which application quality affects the level of student satisfaction in the Independent Product Management study programme. The data collection method used in this study is a questionnaire to collect sample data from 77 students of Ruangguru CAMP Independent Product Management Study Programme. After the data is collected, the data is analysed using the multiple linear regression method to determine whether there is a significant relationship between application quality and user satisfaction. After analysing the data, the results showed that application quality has a positive impact on user satisfaction with a contribution coefficient of 71.4%. Therefore, developers should always optimise application performance to reduce the potential for crashes or other technical problems that may affect the comfort or overall user experience.